PENEGAKAN HUKUM PIDANA TERHADAP PELAKSANAAN AMDAL.â€ (Studi Kasus di Kota Pontianak) - SRI SULASMINI, SH. A.21212072, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2015)
ABSTRACTThis thesis research raised the issue of law enforcement with the research title, TOTHE IMPLEMENTATION OF CRIMINAL LAW ENFORCEMENT EIA.